Ngitus Bali Sebagai Kontrol Sosial Di Desa Murutuwu: Kajian Sosiologis-Teologis terhadap Kearifan lokal Dayak Ma’anyan Kristen Indonesia: Kajian Sosiologis-Teologis terhadap Kearifan lokal Dayak Ma’anyan Kristen Indonesia - Sudianto, Sudianto; Maleh, D.Th, Kinurung (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2025)
This study examines the role of the Ngitus Bali customary law in Murutuwu Village, Central Kalimantan, as a social control mechanism that continues to be upheld despite the influence of modernity and positive law. The Ngitus Bali customary law, involving traditional leaders such as the Pangulu and Mantir, is used to resolve various social disputes, ranging from household issues to land conflicts, with sanctions and reconciliation ceremonies as part of the practice. Although formal laws have been implemented in the village, the community still relies on resolving disputes through customary courts, which is considered more relevant and effective in maintaining social harmony. This research uses a qualitative approach with interviews and observations to explore the community's understanding of customary law and its role in maintaining social stability. The findings indicate that Ngitus Bali functions as a form of social control that strengthens social order and preserves cosmic balance within the Dayak Ma’anyan community in Murutuwu Village.